ปัจจัยที่มีอิทธิพลต่อการมีส่วนร่วมของสมาชิกแจ้งข่าวอาชญากรรม : ศึกษากรณีอำเภอหล่มสัก จังหวัดเพชรบูรณ์ - เกรียงไกร กุญชร (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The purpose of this research was to study participation in informing criminal information of criminal information s members in Lomsak district Phetchabun province in order to study the level of participation factors affecting participation in criminal information s members project. By using simple random sampling, 277 samples were selected. The questionnaires were used for collecting data. For the analysis of the correlation of variable the researcher used program SPSS/PC+, percentage, mean. Pearson Chi - Square and Cramer s V with the statistical significant level at 0.05. The result of the research showed that factors influencing the participation by criminal information s members were age, education and income.